BRAND SWITCHING BEHAVIOUR KONSUMEN MUSLIM ACEH TERHADAP PRODUK MAKANAN DAN MINUMAN PASCA FATWA MUI NO 83 TAHUN 2023 - Ritonga, Nursakinah; Andyna, Cut; Ameliany, Nanda; Sufi, Sufi; Sukmawati, Cut (Universitas Muhammadiyah Tapanuli Selatan, 2025)
The international Boycott, Divestment, Sanctions (BDS) movement is an effort of resistance that does not use violence but by boycotting products affiliated with Israel. In line with the BDS movement, the Fatwa commission of the Indonesian Ulema Council (MUI) on November 8, 2023 issued the latest fatwa number 83 of 2023 regarding the Law of Support for the Palestinian Struggle which confirms that supporting Israeli aggression against Palestine is haram. Aceh Province is the only province that implements the principles of Islamic Shari'ah in Indonesia.This study aims to explain and analyze the effect of e-WOM and Brand Image on consumer behavior to do Brand Switching directly. This type of research is Explanatory Research. The population in this study is the Acehnese Muslim community domiciled in Lhokseumawe City, North Aceh Regency, Bireun Regency who make brand switching in food and beverage product purchase transactions where the population is not known with certainty. The sampling technique in this study used accidental sampling technique. The number of samples was 100 respondents using the Lemeshow formula. Data collection methods using questionnaires and literature studies. The data analysis method used in this study consists of instrument tests in the form of validity tests and reliability tests, normality tests, then path analysis. The results showed that E-WOM has a positive and significant effect directly on Brand Image.Â E-WOM has a positive and significant effect directly on Brand Switching. Brand Image has a positive and significant effect on Brand Switching. The indirect effect of e-WOM on Brand Switching through Brand Image is more explained by the direct effect than the indirect effect.